Pengaruh Faktor L/d terhadap Perilaku Mekanik Balok Kayu Kelapa (Cocos nucifera) The Influence of L/d Factor on the Mechanical Behavior of Coconut Timber Beam (Cocos nucifera) - Kusnindar Abd Chauf (Masyarakat Peneliti Kayu Indonesia, 2008)
The characteristic of coconut timber as anisotropic material should be known for efficiency of flexure structure application. So the influence of L/d factor and the curvature of stress-strain must be known. Based on the coconut timber response towards load, it can be determined its flexure behaviour which consists of deformation, moment, curvature, stiffness and the failure mode. By an experiment it was obtained that the coconut timber at 30 year of age have density (r15) = 0.52 g/cm3, modulus of elasticity (MOE) = 14478 MPa, tensile strength (str //)=31.01 MPa, compression strength (stk //)=18.80 MPa, shear strength (t//) = 10.15 MPa and bending strength (MOR) = 48.96 MPa. The maximum tensile strain is 0.0021 and compressing maximum strain is 0.0108. In this case L/d ³14 represented to determinant the flexure bending failure of coconut timber beam